Lirik Tembang Cianjuran Wanda Panambih dalam Kajian Struktur dan Etnopedagogik - Noni Mulyani; Yayat Sudaryat (JENTERA: Jurnal Kajian Sastra, 2024)
The lyric of Cianjuran Wanda Panambih (Complementary Type) is a kind of lyric that is much inspired by kawih and kesindenan. The use of barels include pelog degung, sorog, salendro, mandalungan, and wisaya.  This research aims to find out and determine the structure of lyric Cianjuran wanda panambih songs based on the structures and ethnopedagogics. In this research, a qualitative approach with a descriptive method is applied. Data is collected through documentation techniques and interview techniques. The source of this research data is the lyrics of Cianjuran song by Mang Bakang.  The results of the research find 33 (thirty-three) lyrics of the song Cianjuran wanda panambih by Mang Bakang, which are observed in terms of structure and ethnopedagogic value. In terms of structure, 10 lyrics are found in the form of pupuh, 18 lyrics in the form of free poetry, and 5 lyrics in the form of insertions. In the lyrics, most images are found, the most dominant theme is humanity, the most dominant tone is educating the reader or reminding the reader, and the most dominant figurative language is the paraphrasing base style. In terms of étnopédagogic, 71 characters are found that refer to the educational value of cultural and national characters based on the Curriculum Center, Research and Development Agency, Ministry of National Education. This research can add insight into the elements of poetry in Cianjuran songs and the emergence of a sense of pride from the community towards Cianjuran songs. AbstrakLirik Tembang Cianjuran Wanda Panambih (Tipe Pelengkap) merupakan tipe lirik tembang yang dipengaruhi oleh kawih dan kepesindenan. Laras yang digunakan meliputi pelog degung, sorog, salendro, mandalungan, dan wisaya. Penelitian ini bertujuan untuk mengetahui dan memaparkan struktur lirik tembang Cianjuran wanda panambih yang dikaji dari struktur dan etnopedagogik. Dalam penelitian ini digunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui teknik dokumentasi dan teknik wawancara. Sumber data penelitian ini adalah lirik tembang Cianjuran karya Mang Bakang. Berdasarkan hasil penelitian ditemukan 33 lirik tembang Cianjuran wanda panambih karya Mang Bakang yang dikaji dari segi struktur dan nilai etnopedagogik. Dari segi struktur ditemukan 10 lirik dalam bentuk pupuh, 18 lirik dalam bentuk puisi bebas, dan 5 lirik dalam bentuk sisindiran. Di dalam lirik tersebut, kebanyakan ditemukan imaji rasa; tema yang paling dominan, yaitu kemanusiaan; nada yang paling dominan, yaitu mendidik pembaca atau mengingatkan pembaca; dan bahasa figuratif yang paling dominan, yaitu gaya bahasa parafrase. Dari segi etnopedagogik ditemukan 71 karakter yang merujuk pada nilai pendidikan karakter budaya dan bangsa yang berdasar pada Pusat Kurikulum Badan Penelitian dan Pengembangan Kementrian Pendidikan Nasional. Penelitian ini bisa menambah wawasan tentang unsur puisi dalam tembang Cianjuran serta timbulnya rasa bangga dari masyarakat terhadap tembang Cianjuran.